Transformation of Public Trust in Restorative Justice by the Prosecutor's Office: An Islamic and Social Law Approach in the Contemporary Era - Hadi Sucipto; Falih Suaedi; Erna Setijaningrum; Mia Amiati; Rachmat Suhaimi Nasution (Faculty of Sharia, IAIN Metro, 2024)
This study examines the transformation of public trust in implementing restorative justice by the prosecutor's office in Indonesia, particularly in a contemporary era that demands a more inclusive and responsive legal approach. Using a qualitative approach, this research combines insights from Islamic law and social studies to examine the factors influencing public trust in restorative justice and the prosecutor's role in resolving conflicts and promoting social harmony. The study gathers insights through in-depth interviews with legal academics, prosecutorial practitioners, and community representatives, aiming to understand their perceptions of the effectiveness and fairness of the restorative justice process. From the Islamic law perspective, the study highlights a normative framework rooted in values of justice, consultation (shura), and restoration (islah), which closely align with the core principles of restorative justice. Social studies provide additional depth by exploring the influence of individual experiences, legal awareness, and public perceptions of the prosecutor's office on trust dynamics. The findings indicate a gradual increase in public trust in restorative justice within Indonesia, reflecting growing acceptance of its potential as an alternative to conventional punitive measures. However, significant challenges persist, particularly regarding transparency and consistency in its implementation by the prosecutor's office. Studies on similar cases worldwide reveal that transparent processes and accountability are essential for maintaining public confidence, underscoring the importance of addressing these gaps in Indonesia. By positioning restorative justice as a culturally resonant and equitable alternative within Indonesia's legal framework, the study provides actionable insights for policymakers and practitioners striving to create a justice system that aligns with societal needs and ethical values.